2018
DOI: 10.14748/bmr.v29.5845
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor in brain diseases

Abstract: The nerve growth factor (NGF) belongs to a family of proteins termed neurotrophins, consisting of NGF, brain-derived neurotrophic factor (BDNF), neurotrophin-3 (NT-3), NT-4/5 and NT-6. Today, NGF is well recognized to mediate a large number of trophobiological actions resulting in neurotrophic, immunotrophic and/or metabotrophic effects. The pathobiology of neurodegenerative diseases, including Alzheimer disease, psychiatric disorders (e.g. depression and schizophrenia) and brain parasitic infections have in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 168 publications
0
11
0
Order By: Relevance
“…It's well known that they also regulate responses to drug abuse, including alcohol [20,21]. Numerous experimental pieces of evidences show that ethanol alters the expression of different neurotrophins in various brain areas [21,22], however little is known about the alcohol effects in non-neuronal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…It's well known that they also regulate responses to drug abuse, including alcohol [20,21]. Numerous experimental pieces of evidences show that ethanol alters the expression of different neurotrophins in various brain areas [21,22], however little is known about the alcohol effects in non-neuronal tissues.…”
Section: Introductionmentioning
confidence: 99%
“…This pathway induces the activation of Ras, a GTPase that phosphorylates the serine/threonine kinase Raf. This latter activates the MAPK cascade, which regulates the activity of several transcription factors, such as the cAMP response element-binding protein (CREB), a transcription factor that translocates in the nucleus to control the expression of anti-apoptotic genes [ 16 , 17 ]. Although the receptor p75 does not contain a catalytic motif, it interacts with several proteins that regulate neuronal survival and differentiation, as well as synaptic plasticity.…”
Section: Nerve Growth Factor - Ngfmentioning
confidence: 99%
“…It is also involved in the regulation of the immune system and the endocrine system, including the adipo endocrine system [ 25 - 27 ]. Consequently, altered expression of NGF and its receptors are involved in many seemingly unrelated diseases, including neuronal disorders (Alzheimer’s and other neurodegenerative diseases) [ 17 , 28 - 30 ], aging [ 31 ], cancer physiology [ 32 - 35 ], ocular diseases [ 36 - 38 ], growth and development [ 33 , 34 , 39 ], autoimmune diseases (rheumatic arthritis, multiple sclerosis, and other autoimmune diseases) [ 40 ], pregnancy, delivery and postpartum [ 41 ], oxidative stress-related diseases [ 42 - 48 ], neuroinflammation caused by parasitic diseases [ 49 - 56 ], and cardiometabolic diseases, such as type 2 diabetes mellitus, obesity and metabolic syndrome [ 57 - 63 ]. Furthermore, pieces of evidence on humans indicate that NGF and its receptors are known to be altered in ethanol-induced toxicity, which is the inducing-cause of brain changes [ 64 , 65 ] and mental retardation [ 66 - 72 ].…”
Section: Nerve Growth Factor - Ngfmentioning
confidence: 99%
“…We have previously examined in the mouse brain (1) that PPAE may disrupt nerve growth factor (NGF) and/or brainderived neurotrophic factor (BDNF), neuropeptides of the neurotrophins family playing crucial roles in the growth, development and survival of nerve cells, also in the pathobiology of cardiometabolic and neuropsychiatric diseases (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58). We found that PPAE affected NGF levels in frontal cortex, striatum, olfactory lobes, hippocampus and hypothalamus.…”
Section: Introductionmentioning
confidence: 99%